The gut bacterium Extibacter muris produces secondary bile acids and influences liver physiology in gnotobiotic mice. (1st January 2021) - Streidl, Theresa; Karkossa, Isabel; Segura Muñoz, Rafael R.; Eberl, Claudia; Zaufel, Alex; Plagge, Johannes; Schmaltz, Robert; Schubert, Kristin; Basic, Marijana; Schneider, Kai Markus; Afify, Mamdouh; Trautwein, Christian; et al.
ABSTRACT: Extibacter muris is a newly described mouse gut bacterium which metabolizes cholic acid (CA) to deoxycholic acid (DCA) via 7α-dehydroxylation. Although bile acids influence metabolic and inflammatory responses, few in vivo models exist for studying their metabolism and impact on the host. Mice were colonized from birth with the simplified community Oligo-MM 12 with or without E. muris . As the metabolism of bile acids is known to affect lipid homeostasis, mice were fed either a low- or high-fat diet for eight weeks before sampling and analyses targeting the gut and liver. Multiple Oligo-MM 12 strains were capable of deconjugating primary bile acids in vitro. E. muris produced DCA from CA either as pure compound or in mouse bile. This production was inducible by CA in vitro . Ursodeoxycholic, chenodeoxycholic, and β-muricholic acid were not metabolized under the conditions tested. All gnotobiotic mice were stably colonized with E. muris, which showed higher relative abundances after HF diet feeding. The presence of E. muris had minor, diet-dependent effects on Oligo-MM 12 communities. The secondary bile acids DCA and surprisingly LCA and their taurine conjugates were detected exclusively in E. muris -colonized mice. E. muris colonization did not influence body weight, white adipose tissue mass, liver histopathology, hepatic aspartate aminotransferase, or blood levels of cholesterol, insulin, and paralytic peptide (PP). However, proteomics revealed shifts in hepatic pathways involved in amino acid, glucose, lipid, energy, and drug metabolism in E. muris -colonized mice. Liver fatty acid composition was substantially altered by dietary fat but not by E. muris. In summary, E. muris stably colonized the gut of mice harboring a simplified community and produced secondary bile acids, which affected proteomes in the liver. This new gnotobiotic mouse model can now be used to study the pathophysiological role of secondary bile acids in vivo .